The experience of organization of research work at Ukrainian secondary schools in the second half of the twentieth century (Pedagogy of Higher and Secondary Education, 2014)
Irza V. I. The experience of organization of research work at Ukrainian secondary schools in the second half of the twentieth century.The article deals with the retrospective analysis of existing pedagogical experience of organization of research work at Ukrainian secondary schools during the period 1945-1991. It is spoken in detail about the technique of experiments at the teaching-experimental plot of the school. The features of the organization of research work of pupils in different regions of Ukraine are described.
Keywords: experiment; research work; observation; teaching-experimental plot; agricultural research